105 Loop taping for heel fat pad syndrome: A randomized controlled crossover clinical trial. (25th January 2023) - Chang, Alison; Sørensen, Thomas; Skov, Katrine; Rathleff, Michael; Riel, Henrik; Lyng, Kristian; Christensen, Marianne
Abstract : Introduction: Heel fat pad syndrome (HFPS) is the second leading cause of plantar heel pain. Clinical practice guidelines recommend conservative treatments for HFPS (activity modification, arch taping, and viscoelastic heel-cups). Alarmingly, the evidence for managing HFPS is scant and no well-executed randomised trials exist to support specific treatments. We aim to examine the effect of a novel heel fat pad loop taping on pain and function for HFPS. Materials and Methods: In this two-arm crossover, participant-blinded RCT, participants with HFPS are block-randomized into either AB or BA interventions (A=loop taping that encircles/bunches the fat pad to centralize it and enhance its fullness and resilience to compression, B=control taping that mimic the loop taping without any force/pressure or attempt to bunch/centralize the fat pad) with a 4-to-7-day between-intervention washout period. The primary outcome is pain during the most pain-aggravating activity selected by participants (30-sec single-leg standing or 20-meter barefoot walking). Secondary outcomes are worst pain in the past 24 hours, foot health/function using the Foot Health Status Questionnaire, and global rating of change. We also assessed mechanistic outcomes of ultrasound-measured heel fat pad thickness and pressure-algometer-measured pressure pain thresholds. Results: This pre-registered RCT will be completed in December 2022. 19 participates are needed to detect a 2-point greater pain reduction for loop vs. control taping. We have eligibility-screened 17 participants, enrolled and completed data collection in 2. Conclusion: Findings of this first RCT examining clinical and mechanistic effects of loop taping will provide much-needed evidence on effective non-pharmacological managements of HFPS.